Branched‐chain in situ hybridization for κ and λ light chains: A powerful ancillary technique for determining B‐cell clonality in cytology samples. Issue 3 (2nd November 2015) - Arora, Kshitij; Chebib, Ivan; Zukerberg, Lawrence; Gandhi, Manoj; Rivera, Miguel; Ting, David; Deshpande, Vikram
Abstract : BACKGROUND: Current immunohistochemical and in situ hybridization (ISH) assays are generally inconclusive for clonality unless plasmacytic differentiation is present. This study examined a series of cytology specimens and explored the ability of a branched‐chain RNA (bRNA) ISH assay for immunoglobulin κ constant ( IGKC ) and immunoglobulin λ constant ( IGLC ) to detect a clonal population of B lymphocytes. METHODS: Pathology databases were used to identify fine‐needle aspiration biopsies (n = 28) and exfoliative cytology samples (n = 20). Demographic, flow cytometry, and excision biopsy results were recorded. bRNA ISH was performed on the Leica Bond platform with the following probes: IGKC, IGLC, immunoglobulin λ‐like polypeptide 5 ( IGLL5 ), and a housekeeping gene (HKG). RESULTS: The bRNA ISH assay was validated with 30 surgical biopsies. On bRNA ISH, a clonal B‐cell population (light‐chain ratio > 10:1) was detected in 22 of 28 cases with a final diagnosis of lymphoma. In 2 cases, a κ predominance was present, although the ratio was <10:1. Eleven of the 17 κ‐clonal lymphomas also expressed IGLL5, the latter recognized by the presence of an intranuclear signal. Two B‐cell lymphomas lacked IGKC and IGLC, whereas 2 cases were negative for the HKG. In 12 of the 20 cases with reactive lymphoid tissue, bRNA ISH identified a polyclonal lymphoid population. No light‐chain messenger RNA was detected in 6 cases (typically those associated with very few B cells). CONCLUSIONS: The automated bRNA ISH platform is a robust technique for detecting a clonal B‐cell population in cytology material. Cancer Cytopathol 2016;124:203–212. © 2015 American Cancer Society . Abstract : The automated branched‐chain RNA in situ hybridization platform is a robust platform that detects a clonal B‐cell population in cytology material.